Proceedings of the VII European Congress on Computational Methods in Applied Sciences and Engineering (ECCOMAS Congress 2016) 2016
DOI: 10.7712/100016.2450.8838
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Aerodynamic Shape Optimization Framework for Robust Design of Airfoils Using Surrogate Models

Abstract: Abstract. This paper deals with developing an efficient Robust Design Optimization (RDO) framework. The goal is to obtain an aerodynamic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…At this condition a strong near-normal shock wave is present over the upper surface and the addition of a shock control bump is expected to considerably reduce drag by weakening the shock intensity. Previous studies have been done for the aerodynamic shape optimization of airfoils under uncertainty [15,16]. However, no focus was given in obtaining a robust global solution that reduces both the number of optimization iterations and function evaluations in the uncertainty quantification stage.…”
Section: Problem Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this condition a strong near-normal shock wave is present over the upper surface and the addition of a shock control bump is expected to considerably reduce drag by weakening the shock intensity. Previous studies have been done for the aerodynamic shape optimization of airfoils under uncertainty [15,16]. However, no focus was given in obtaining a robust global solution that reduces both the number of optimization iterations and function evaluations in the uncertainty quantification stage.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Schillings [12] and Maruyama [15] have shown that for UQ, the accuracy of the surrogate can be improved if the initial sampling follows the distribution of the input uncertainties ξ. In the design of experiments, more samples should be placed along the mean, than along the tails of the input PDFs.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…The use of Robust Optimization in aerodynamic shape optimization is increasing in popularity in order to come up with designs less sensitive against operational and geometrical uncertainties [1,2,3,4] . In opposition to deterministic optimization, where the Quantity of Interest, QoI, is a single value to be optimized, in robust optimization the QoI is a random variable.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the complexity of the optimization increases exponentially with the number of design parameters [5]. On the other hand, at each iteration of the optimization, a complete propagation of the uncertainty is required in order to come up with an accurate estimation of the 2 Christian Sabater and Stefan Görtz statistic to be minimized [3]. A possible solution to the first problem is the use of adjoint methods [6].…”
Section: Introductionmentioning
confidence: 99%
“…For multi-disciplinary optimisation see Refs 20-22. For design, tools based on surrogate models (23) , and tools for robust design (design under uncertainty) (24) are also considered.…”
Section: Introductionmentioning
confidence: 99%